Letter - Lizaso, Jose I. de
027-0030-001 Euzkadi Ordezkaritza BASQUE DELEGATION, 14, ECCLESTON SQUARE, LONDON, S.W.1. TEL: VICTORIA 0926. 13th April, 1940, Dear Mr. Tewson, Confirming my telephone conversation of this morning, I very much appreciate your kindness in agreeing to take up the case of my two friends who, as I explained, I am very anxious to help. Here are the particulars:- Julian Hickman Urrutia, whom I am particularly concerned about, has been in El Dueso prison for three years, being released as a result of pressure by the British Consul. He is 33 years old and was employed in the great iron works of Bilbao, Altos Hornos de Vizcaya, for 13 years as a fully qualified draftsman; he also acted as assistant to the chief Engineer, and is therefore something more than an ordinary draftsman. Jesus Hickman Urrutia, his brother, is 41 years old, and was also employed at Altos Hornos de Vizcaya as a draftsman, for over 23 years. They come of a good family, whom I know very well, and I am personally prepared to guarantee them in any way required. Although they are Basques, they are actually British subjects, on account of a British grandfather, and are ready to join any union which may be desirable. They are in very poor circumstances at present and receiving Public Assistance from the London County Council. I shall esteem it a very great favour if you can do anything possible to help me to solve the problem of aiding my friends. With kind regards, Yours very sincerely, Jose I. de Lizaso. C. Tewson, Esq. Trades Union Congress. Transport House, S.W.1. 292/946/27/30